New interactions 2 : reading and writing - Hartmann, Pamela; Mentel, James (London : McGraw-Hill Education (UK), 2020)
The seventh edition of New Interactions 2: Reading and Writing is a fully revised academic skills series designed to prepare students for success in higher education. This edition focuses on the development of critical thinking and the writing process through high-interest, contemporary themes. It utilizes powerful digital tools and a student-centered approach to facilitate the transition from lower-order to higher-order thinking skills, providing a dynamic and flexible learning environment for English for Academic Purposes (EAP) learners.
Keywords: English language -- Textbooks for foreign speakers; English language -- Composition and exercises; Academic writing -- Study and teaching